Evaluation of Graft Fibrosis, Inflammation, and Donor-specific Antibodies at Protocol Liver Biopsies in Pediatric Liver Transplant Patients: A Single-center Experience. Issue 1 (January 2022) - Pinon, Michele; Pizzol, Antonio; Chiadò, Cristina; David, Ezio; Chiusa, Luigi; Dell'Olio, Dominic; Isolato, Giuseppe; Amoroso, Antonio; Deaglio, Silvia; Catalano, Silvia; Tandoi, Francesco; Romagnoli, Renato; et al.
Abstract : Background: The impact of graft fibrosis and inflammation on the natural history of pediatric liver transplants is still debated. Our objectives were to evaluate the evolution of posttransplant fibrosis and inflammation over time at protocol liver biopsies (PLBs), risk factors for fibrosis, presence of donor-specific antibodies (DSAs), and/or their correlation with graft and recipient factors. Methods: A single-center, retrospective (2000–2019) cross-sectional study on pediatric liver transplant recipients who had at least 1 PLB, followed by a longitudinal evaluation in those who had at least 2 PLBs, was conducted. Fibrosis was assessed by the Liver Allograft Fibrosis Semiquantitative score, inflammation by the rejection activity index, DSAs by Luminex. Results: A total of 134 PLBs from 94 patients were included. Fibrosis was detected in 87% (30% mild, 45% moderate, and 12% severe), 80% in the portal tracts. There was an increase in fibrosis between the 1–3 and the 4–6 y group ( P = 0.01), then it was stable. Inflammation was observed in 44% (30% mild, 13% moderate, and 1% severe), 90% in the portal tracts. Anti-HLA II (IgG) DSAs were detected in 14 of 40 (35%). Portal fibrosis was associated with portal inflammation in the 1–3 y group ( P = 0.04). Low immunosuppression levels were correlated with sinusoidal fibrosis ( P = 0.04) and DSA positivity ( P = 0.006). There was no statistically significant correlation between DSA positivity and the presence of graft fibrosis or inflammation. Conclusions: This study corroborates the concept of an early evolution of silent graft fibrosis. Suboptimal immunosuppression may play a role in the development of fibrosis and DSAs.